ChemInform Abstract: The Dimeric [V2O4F6]4‐ Vanadium Oxide‐Fluoride Anion in Na2(M(H2O)2) (V2O4F6) (M: Co2+, Ni2+, and Cu2+). Issue 3 (22nd January 2013) - Donakowski, Martin D.; Vinokur, Anastasiya I.; Poeppelmeier, Kenneth R.
Abstract The new compounds (IV) and (VI) crystallize isostructurally in the monoclinic space group P21/c with Z = 2 (single crystal XRD).